Segmental Maternal UPD of Chromosome 7q in a Patient With Pendred and Silver Russell Syndromes-Like Features - Cirello, Valentina; Giorgini, Valentina; Castronovo, Chiara; Marelli, Susan; Mainini, Ester; Sironi, Alessandra; Recalcati, Maria Paola; Pessina, Marco; Giardino, Daniela; Larizza, Lidia; Persani, Luca; Finelli, Palma; et al. (Frontiers in Genetics, 2018)
Pendred syndrome (PS) is an autosomal recessive disorder due to mutations in the SLC26A4 gene (chr7q22.3) and characterized by sensorineural hearing loss and variable thyroid phenotype. Silver-Russell syndrome (SRS) is a heterogeneous imprinting disorder including severe intrauterine and postnatal growth retardation, and dysmorphic features. Maternal uniparental disomy of either the whole chromosome 7 (upd(7)mat) or 7q (upd(7q)mat) is one of the multiple mechanisms impacting the expression of imprinted genes in SRS, and is associated with milder clinical features. Here, we report genetic and clinical characterization of a female child with PS, postnatal growth retardation and minor dysmorphic features. A gross homozygous deletion of SLC26A4 exons 17-20 was suspected by Sanger sequencing and then confirmed by array-CGH. Moreover, an insertion of about 1 kb of the CCDC126 gene (7p15.3), which does not appear to be clinically relevant, was detected. The possible occurrence of a balanced rearrangement between 7p and 7q was excluded. The absence of the deletion in the father led to the investigation of upd, and microsatellite segregation analysis revealed a segmental 7q (upd(7q)mat), leading to SLC26A4 homozygosity and responsible for both PS and SRS-like traits. The proband matched 3 out of 6 major SRS criteria. In conclusion, this is the first report of uniparental isodisomy encompassing almost the whole long arm of chromosome 7 resulting in PS and SRS-like features. Whereas the inner ear phenotype of PS is typical, the clinical features suggestive of SRS might have been overlooked.